HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL PICTURE AND PICTURE DAN STAD MEMPERHATIKAN MOTIVASI - Isra Selvy Rolina; Pujiati Pujiati; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2015)
This study aimed to determine the ratio and improving student learning outcomes using models Picture and Picture and STAD regarding to the motivation of economic subjects in class X of SMAN 15 Bandarlampung. A population of this study were 232 students and 74 samples. The sample was determined through cluster random sampling technique. Collecting data was through testing, documentation and questionnaires. Data analysis used was ANOVA and T-test two independent samples. The results showed: (1) There are differences in learning outcomes of students who are taught using learning models Picture and Picture and STAD (2) The results of student learning using models Picture and Picture is higher than STAD to students who have higher learning interest, (3) The results of student learning using models Picture and Picture were lower than STAD to students who have low learning interest, (4) There is an interaction between learning model with the motivation of economic subjects to the students' learning outcomes.Penelitian ini bertujuan untuk mengetahui perbandingan dan peningkatan hasil belajar siswa menggunakan model Picture and Picture dan STAD dengan memperhatikan motivasi pada mata pelajaran ekonomi siswa kelas X di SMAN 15 Bandarlampung. Populasi berjumlah 232 siswa dan 74 sampel. Sampel ditentukan melalui teknik cluster random sampling. Pengumpulan data melalui tes, dokumentasi dan angket. Analisis data yang digunakan adalah ANOVA dan T-test Dua Sampel Independen. Hasil penelitian menunjukkan: (1) Ada perbedaan hasil belajar siswa yang diajar menggunakan model pembelajaran Picture and Picture dan STAD (2) Hasil belajar siswa menggunakan model Picture and Picture lebih tinggi dibandingkan STAD terhadap siswa yang minat belajarnya tinggi, (3) Hasil belajar siswa menggunakan model Picture and Picture lebih rendah dibandingkan STAD terhadap siswa yang minat belajarnya rendah, (4) Ada interaksi antara model pembelajaran dengan motivasi terhadap hasil belajar siswa.Kata kunci: hasil belajar, motivasi, picture and picture, STAD.